Challenges in Research and Community Engagement During the COVID-19 Pandemic in Resource-Limited Settings: Qualitative Analysis with Epidemic Preparedness Implications - Kaawa-Mafigiri, David; Muyomba, Dickson; Kisakye, Irene Sheila; Semakula, Daniel; Sewankambo, Nelson K. (My University, 2023)
When WHO declared the SARS-CoV-2 respiratory virus pandemic in 2020, Uganda was unprepared to prevent and control its spread and severe impact on peoples’ lives including management of COVID-19 patients. We planned to conduct a community engagement and risk communication (CERC) trial during the pandemic but before implementation we conducted a baseline study. A community baseline face-to-face mixed-methods study with quantitative survey and qualitative research (in-depth interviews, key informant interviews, focus group discussions, and household conversations) was implemented in 15 parishes (6 and 9 in Kawempe and Nakawa divisions respectively) of Kampala Capital City Authority, Uganda. We employed a multistage sampling strategy that allocated parishes and villages based on their proportional contribution to the overall population for the planned subsequent CERC trial. The baseline study, was conducted during the pandemic from July 2020 to February 2021. The 852 respondents with median age 32 years (IQR 25-42), majority were females (n=610, 73·05%), and household heads (n=391, 46·5%) followed by spouses of household heads (n=305, 36·1%) and children (n=68, 8%). Most were low-income earners and others middle-income workers. Some had tertiary education (n=206, 24·2%), ordinary level (n=195, 23·3%), primary education (n=201, 24·01%), and no formal education (n=142, 16%). Conducting research and community engagement had many challenges, categorized into three main interrelated domains: a) scientific process implementation challenges b) those associated with the social, cultural, and political context of the research, and c) budgetary and funding inadequacies. The lessons learned from the conduct of community engagement and community research during the COVID-19 pandemic should become a cornerstone for preparedness for the next severe epidemic or pandemic. The practical application of key concepts like CE, risk communication, conventional qualitative research methods must be examined to make them more applicable and responsive during complex and dynamic infectious disease epidemics and pandemics.